Health Scares: Tracing Their Nature, Growth and Spread - Kate MacKrill; Michael Witthöft; Simon Wessely; Keith J. Petrie (Clinical Psychology in Europe, 2023)
[Background] Health scares are highly publicised threats to health that increase public concern and protective behaviours but are later shown to be unfounded. Although health scares have become more common in recent times, they have received very little research attention. This is despite the fact that health scares often have negative outcomes for individuals and community by affecting health behaviours and causing high levels of often unnecessary anxiety. [Method] In this paper we undertook a review and analysis of the major types of health scares as well as the background factors associated with health scares and their spread. [Results] We found most health scares fell into seven main categories; environmental contaminants, food, malicious incidents, medical treatments, public health interventions, radiation from technology and exotic diseases. For most health scares there are important background factors and incident characteristics that affect how they develop. Background factors include conspiracy theories, trust in governmental agencies, anxiety, modern health worries and wariness of chemicals. Incident characteristic include being newly developed, not understood or unseen, man-made rather than natural and whether the incident is out of personal control. We also identified the aspects of traditional and social media that exacerbate the rapid spread of health scares. [Conclusion] More research is needed to identify the characteristics of media stories that intensify the levels of public concern. Guidelines around the media’s reporting of health incidents and potential health threats may be necessary in order to reduce levels of public anxiety and the negative public health impact of health scares.